2022
DOI: 10.3390/ijerph19010573
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sleep Characteristic Changes on Nurses’ Quality of Life during Their Transition to Practice: A Prospective Cohort Study

Abstract: Aim: To explore the effect of changes in sleep characteristics on changes in quality of life during the transition period of new graduate nurses. Background: Sleep problems among nurses are associated with negative physical and psychological consequences. Methods: This prospective cohort study was conducted at a tertiary hospital in South Korea. Participants included 88 newly graduated nurses. Data were collected twice, prior to shift work and after 4 months of working as a nurse, via online structured self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…1 In a recent study of 88 newly graduated nurses working in a tertiary hospital in South Korea, Kim and Lee found a significant decline in subjective sleep quality over the first four months of undertaking shift work as a nurse, which was associated with a decline in quality of life. 23 Similarly, Donovan and colleagues reported emotional, physical and mental exhaustion was often attributed to sleep deprivation during the graduate year of nursing and midwifery. 24 Epstein and colleagues also explored sleep during the graduate year and found graduate nurses had limited and potentially counterproductive strategies to cope with fatigue.…”
Section: Healthy Sleep and Nursing Editorialmentioning
confidence: 98%
“…1 In a recent study of 88 newly graduated nurses working in a tertiary hospital in South Korea, Kim and Lee found a significant decline in subjective sleep quality over the first four months of undertaking shift work as a nurse, which was associated with a decline in quality of life. 23 Similarly, Donovan and colleagues reported emotional, physical and mental exhaustion was often attributed to sleep deprivation during the graduate year of nursing and midwifery. 24 Epstein and colleagues also explored sleep during the graduate year and found graduate nurses had limited and potentially counterproductive strategies to cope with fatigue.…”
Section: Healthy Sleep and Nursing Editorialmentioning
confidence: 98%
“…Participants responded to the questions using a 5-point scale, and the total sum of these responses yields a final score ranging from 0 to 28. The total score allows for the differentiation of following severity levels: absence of insomnia (0-7), subthreshold insomnia (8)(9)(10)(11)(12)(13)(14), moderate insomnia (15)(16)(17)(18)(19)(20)(21), and severe insomnia (22-28).…”
Section: Insomnia Severity Index (Isi)mentioning
confidence: 99%
“…Studies reporting prevalence rates between 60% to 75% evaluated deprived sleep quality [7,8]. Studies have additionally connected insufficient rest with an expanded number of clinical blunders among medical staff and other work-related injuries [10]. Long hours in nursing have a variety of effects on nurses' quality of life, the most prevalent of which is a reduction in sleep quality [11].…”
Section: Introductionmentioning
confidence: 99%
“…Good sleep is critical for both mental and physical well-being, as well as a high quality of life, which plays a crucial role in maintaining human homeostasis and promoting health [ 1 ]. But a lot of things about modern life, like staying up late working, engaging in more activities at night, and using screens for electronic media more often, can cause sleep issues [ 2 , 3 , 4 ]. Numerous studies have shown a constant link between poor sleep quality and multimorbidity, such as mental dysfunctions, cardiovascular disease, diabetes and obesity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%